BIMBINGAN PEMBUATAN COMPANY PROFILE UNTUK MENDUKUNG PROMOSI BISNIS KULINER UMKM WARUNG HARUM - Rena Feri Wijayanti; Lina Budiarti; Joni Dwi Pribadi; Erlangga Andi Sukma; Abdul Waris (P3M Politeknik Negeri Malang, 2023)
When talking about current business developments, there has been a lot of talk about where 2023 is the year towards a recession situation. This condition will certainly have an impact on all aspects of the main activities of the business sector, which inevitably must be prepared to face heavy burdens not only due to intense competition, but also sluggish conditions which can reduce business turnover. Of course, it's not strange if the end of all business is to get maximum income in which it must be considered as profit. Various efforts need to be made by all business scales, including MSMEs. Even though there is a long story that MSMEs always manage to get through even difficult situations, of course you can't if you just wait for what will happen in the future. One effort that can be done by adjusting all the resources owned by a place of business is to strengthen the business name and promote it more broadly through a business profile (company profile) that can be reached by the whole community as potential customers. A business profile that can highlight various characteristics of a place of business not only enhances a positive image in the eyes of consumers but also can reach some opportunities to bring in investors who can work together to develop the business.